Pengaruh Pertumbuhan Ekonomi, Inflasi, Angkatan Kerja dan Kemiskinan terhadap Upah Minimum Regional di Provinsi Jawa Barat - Velin Aulia Febrianti; Sodik Dwi Purnomo; Anisa Fatmawati (Universitas Batanghari Jambi, 2026)
The determination of Regional Minimum Wage (UMK) serves as a strategic policy instrument to maintain workers' purchasing power and regional economic stability. This study aims to analyze the effects of Economic Growth, Inflation Rate, Labor Force Participation Rate, and Poverty Rate on UMK in West Java Province. A descriptive quantitative approach was employed using panel data regression across 27 regencies/cities from 2010 to 2025, yielding a total of 432 observations. The findings reveal that Economic Growth and Inflation Rate have a negative and significant effect on UMK, indicating that GRDP expansion and price increases have not been optimally converted into drivers for wage increases. Conversely, the Labor Force Participation Rate shows a positive and significant effect, suggesting that higher labor participation provides a tangible push toward wage adjustments. Meanwhile, the Poverty Rate exerts a negative and significant influence, demonstrating that high poverty levels tend to hold back the pace of UMK adjustments. Policy implications require the Regional Wage Council to revise the wage-setting formulation so that it does not rely rigidly on economic growth alone, but rather adapts more flexibly to price stability, labor force quality enhancement, and integrated regional poverty alleviation.